Frequent amplification of c-myc in ground squirrel liver tumors associated with past or ongoing infection with a hepadnavirus. - Transy, C (1992)
Persistent infection with hepatitis B virus (HBV) is a major cause of hepatocellular carcinoma (HCC) in humans. HCC has also been observed in animals chronically infected with two other hepadnaviruses: ground squirrel hepatitis virus (GSHV) and woodchuck hepatitis virus (WHV). A distinctive feature of WHV is the early onset of woodchuck tumors, which may be correlated with a direct role of the virus as an insertional mutagen of myc genes: c-myc, N-myc, and predominantly the woodchuck N-myc2 retroposon. In the present study, we searched for integrated GSHV DNA and genetic alterations of myc genes in ground squirrel HCCs. Viral integration into host DNA was detected in only 3/14 squirrel tumors and did not result in insertional activation of myc genes, despite the presence of a squirrel locus homologous to the woodchuck N-myc2 gene. This suggests that GSHV may differ from WHV in its reduced ability to induce mutagenic integration events. However, the high frequency of c-myc amplification (6/14) observed in ground squirrel HCCs indicates that myc genes might be preferential effectors in the tumorigenic processes associated with rodent hepadnaviruses, a feature not reported so far in HBV-induced carcinogenesis. Together with previous observations, our results suggest that hepadnaviruses, despite close genetic and biological properties, may use different pathways in the genesis of liver cancer.